Integration of Kelik Lang Dance Learning for Suku Dalam Children as a Medium for Developing Motor Skills and Character in Early Childhood in Jambi Province - zari, Nurmalinda; Hartono, Hartono; Jazuli, Muhammad; Kausari, Dini; Izza, Hillia (IJORER : International Journal of Recent Educational Research, 2026)
This study aims to examine the integration of Kelik Lang dance learning for Suku Dalam children as a medium for developing motor skills and character building for early childhood in Jambi Province. Kelik Lang dance is a traditional dance rich in cultural values, togetherness, and discipline. The research method used is a qualitative approach with an ethnopedagogical study design. Data were collected through observation, interviews, and documentation of children, traditional leaders, and educators. Methodologically, the evaluation of children's motor development relies on a specific conceptual framework for early childhood gross motor assessment, focusing on coordination, balance, and flexibility. The results of the study indicate that Kelik Lang dance learning can improve children's gross motor coordination, balance, and flexibility, while also instilling character values such as cooperation, responsibility, and respect for local culture. The integration of traditional dance in early childhood learning is an effective strategy for developing children's potential holistically based on local wisdom. Learning based on local arts and culture needs to be developed sustainably as part of contextual early childhood education.